Negotiating employability: migrant capitals and networking strategies for Zimbabwean highly skilled migrants in the UK - Thondhlana, Juliet; Madziva, Roda; McGrath, Simon (Wiley, 2016)
In this paper we focus on highly skilled migration from Zimbabwe to the UK, exploring these migrants’ social capital sources/structures and content. In doing so we pay attention to routes of migration and how they shape migrants’ networking capabilities and patterns. We further take a Bourdieusian perspective and explore the intersection between social capital and cultural capital in the process of migrants’ negotiation of employment opportunities, giving closer attention to how the distinctive habitus associated with being highly skilled migrants from Zimbabwe shape migrants’ attitudes towards work. By exploring the interplay between external processes and internalised structures, we bring to the fore the multiple positioning of our participants, who we see not as simply depending on social networks, but as complex actors whose negotiation of employability in the UK is shaped by various factors including intersecting aspects of differentiation.